The relevance of the European Audit Reform from the perspective of auditors - Victor Nunes; Fábio Henrique Ferreira de Albuquerque; Gabriel Correia Alves (Suma de Negocios, 2021)
This study aims to draw conclusions about the impact of the European Audit Reform (EAR) on the role and independence of external auditors from the perspective of these professionals in Portugal. Given the innovative and practical nature of this research, the measures implemented by EAR were selected for analysis to clarify and better define the auditors’ role, reinforce the auditors’ professional independence and scepticism, and increase the supervision of the auditors. Data were collected from a questionnaire sent to the auditors (ROC), resulting in a sample of 89 professionals. Descriptive analyses, the Mann-Whitney test, as well as multivariate analyses comprised by factorial analysis and a logistic regression were carried out. The findings pointed to levels of agreement generally higher than the disagreement for the different measures implemented by the EAR, which are amplified in regards to the auditors’ answers that considered the introduction of the EAR as fundamental.